A case report of ventricular suicide following transcatheter aortic valve replacement for severe aortic stenosis in a patient with hypertrophic cardiomyopathy: the danger of abrupt afterload reduction - Kirtivardhan Vashistha; Akshat Banga; Ramzi Khalil; Jian Hu; Pietro Bajona; Jennifer Keeley; Srinivas Murali; Craig Alpert; Robert Biederman; Victor Farah; Vinh Nguyen (The Egyptian Heart Journal)
Abstract Background We describe a patient with severe aortic stenosis (AS) developing obstructive shock immediately following transcatheter aortic valve replacement (TAVR) secondary to a unique phenomenon termed “ventricular suicide.” Abrupt withdrawal of chronically high afterload may lead to mid-ventricular systolic collapse ± left ventricular outflow tract (LVOT) obstruction in the setting of hyperdynamic contractility, as seen in hypertrophic cardiomyopathy (HCM). Case presentation An 88-year-old male with severe symptomatic AS presented with worsening dyspnea. Given his high surgical risk and frailty, he underwent TAVR. The patient had a history of persistent atrial fibrillation, hypertension, hyperlipidemia, prior cerebellar stroke, and severe AS. Post-TAVR, he experienced a significant blood pressure drop, leading to shock. Investigations revealed hyperdynamic left ventricular (LV) function, cavitary obliteration, and systolic anterior motion of the mitral valve. Management included intravenous fluids and phenylephrine, which stabilized his condition. He was discharged on a beta-blocker and remained asymptomatic with a normally functioning TAVR prosthesis one month post-discharge. Conclusion HCM and its phenocopies are associated with worse outcomes post-TAVR. Prophylactic beta-blockade and hydration may prevent hemodynamic collapse in patients with anatomic substrates for ventricular suicide.